Preventive actions of allergen immunotherapy: the facts and the effects in search of evidence - Irene Martignago (Clinical and Molecular Allergy, 2017)
Abstract Allergen immunotherapy (AIT) is the only treatment that works on the causes of allergy. Available AIT nowadays are subcutaneous immunotherapy (SCIT) and sublingual immunotherapy (SLIT) for allergic rhinitis and asthma, while for allergy to Hymenoptera venom only subcutaneous route is recommended. A bulk of trials and meta-analyses demonstrated that efficacy and safety of AIT in decreasing allergic clinical symptoms and use of rescue medications, while its preventive capacity is yet under investigation. The most important of these effects is the prevention of potentially fatal anaphylactic reactions to Hymenoptera stings by venom immunotherapy (VIT). A certain number of studies thus far available showed that AIT, in both forms, is able to prevent the progress of allergic rhinitis into asthma and the development of new sensitizations. These effects should be related to the mechanisms of action of AIT. In fact, it has been demonstrated that both SCIT and SLIT are able to modify the allergen presentation by dendritic cells, with result in modification of the phenotype of allergen-specific T cells, switching from the typical of allergic inflammation Th2-type response to a Th1-type one. Also allergen-specific T regulatory (Treg) cells play a pivotal role by producing suppressive cytokines, such as IL-10 and TGF-beta. However, the only plain evidence of a preventive effect concerns VIT, while the other outcomes need to be furtherly investigated.